Distinct Effect of TCF4 on the NFκB Pathway in Human Primary Chondrocytes and the C20/A4 Chondrocyte Cell Line. (July 2014) - Landman, E.B.M.; Periyasamy, P.C.; van Blitterswijk, C.A.; Post, J.N.; Karperien, M.
Objective: Previous studies indicated a difference in crosstalk between canonical WNT pathway and nuclear factor-κB (NFκB) signaling in human and animal chondrocytes. To assess whether the differences found were dependent on cell types used, we tested the effect of WNT modulation on NFκB signaling in human primary articular chondrocytes in comparison with the immortalized human costal chondrocyte cell line C20/A4. Design: We used gene expression analysis to study the effect of WNT modulation on IL1β-induced matrix metalloproteinase (MMP) expression as well as on WNT and NFκB target gene expression. In addition, we tested the involvement of RelA and TCF4 on activation of the WNT and NFκB pathway by TCF/LEF and NFκB reporter experiments, respectively. Results: We found an inhibitory effect of both induction and inhibition of WNT signaling on IL1β-induced MMP mRNA expression in primary chondrocytes, whereas WNT modulation did not affect MMP expression in C20/A4 cells. Furthermore, TCF/LEF and NFκB reporter activation and WNT and NFκB target gene expression were regulated differentially by TCF4 and RelA in a cell type–dependent manner. Additionally, we found significantly higher mRNA and protein expression of TCF4 and RelA in C20/A4 cells in comparison with primary chondrocytes. Conclusions: We conclude that WNT modulation of NFκB is, at least in part, cell type dependent and that the observed differences are likely because of impaired sensitivity of the NFκB pathway in C20/A4 cells to modulations in WNT signaling. This might be caused by higher basal levels of TCF4 and RelA in C20/A4 cells compared to primary chondrocytes.